Prosopis Africana Extracts as Potential Natural Alternatives to Synthetic Antibiotics and a Key for Sustainable Broiler Production: a Review - John, Alagbe Olujimi (MultiTech Publisher, 2024)
The chicken sector is more vulnerable to antimicrobial resistance, the buildup of toxic or dangerous residues in meat and eggs, and environmental contamination as a result of the widespread and careless use of antibiotics in most nations. Natural solutions, such as medicinal plants, are required to address these issues. These plants have been shown to contain a variety of phytochemicals, including phenols, flavonoids, terpenoids, tannins, alkaloids, and saponins. These chemicals endow plants with a multitude of medicinal qualities. One of the many alternatives to antibiotics is Prosopis africana extract, which includes stem bark, leaves, roots, and their essential oils. Antioxidant, antibacterial, antifungal, anti-helminthic, antiviral, hepatoprotective, immune-stimulatory, and antimicrobial properties are among the many pharmacological activity of P. africana preparations. They are also an abundant supplier of vital minerals and amino acids that support enzyme function and provide defense against the effects of oxidative stress. Using extracts from Prosopis africana is the way forward for effective chicken production, environmental sustainability and food hygiene.